THE INFLUENCE OF THE USE OF CANVA-BASED LEARNING VIDEOS ON STUDENTS' LEARNING OUTCOMES ON ANIMAL BREEDING MATERIALS AT SDN 32 BANDA ACEH - Muthmainnah, Hayatul; Yamin, M.; Safiah, Intan (Elementary Education Research, 2024)
Education in the 21st century is different from previous centuries. Education in the 21st century is constructional, utilizing information technology and technology. Therefore, teachers are required to be more creative and innovative in creating learning that can foster students' curiosity. Choosing learning media that is appropriate to current developments is the main factor in success in learning. One of them is Canva, which is a graphic design application that can be developed in the abstract science learning process. The Canva application provides various features and various interesting templates that teachers can access to present teaching material in a semi-concrete way. This research aims to determine the effect of using Canva-based learning videos on students in animal breeding material at SDN 32 Banda Aceh which consists of two classes, namely class VI/A and class VI/B. In this research, a quantitative approach was used, True Experimental Designs research type using Posttest Only Control Design. Data analysis techniques use SPSS Statistics 24 and hypothesis testing using independent t-tests. the results of hypothesis testing with independent t-test statistics obtained a significance (2-tailed) of 0.000 0.05. So the basis for decision making is that H is accepted and H is rejected. So there is a significant effect of using Canva-based learning videos on students in animal breeding material at SDN 32 Banda Aceh.